Determination of Mechanical Properties of Materials by Small Punch and Other Miniature Testing Techniques: Proceedings of the 5th International Small Sample Test Techniques Conference SSTT2018 - Robert Lancaster (Swansea University Institute of Structural Materials, 2018)
Topics include Small Scale Testing for Tensile and Fracture Behaviour of Steel, Alternative Miniaturised Test Methods, Impression Creep, Miniaturised Tensile Testing, Small Scale Testing of Advanced Materials, Small Scale Creep Testing, Small Scale Testing Methodologies and Standardisation.